An Examination of Teaching Presence in an Accelerated Online Bachelor of Business Administration Course - Krier, Karen; Ching, Yu-Hui; Lowenthal, Patrick (Online Learning, 2025)
A quantitative content analysis study was conducted to examine teaching presence in an online accelerated Bachelor of Business Administration (BBA) course. Analyzing various course materials, this study identifies patterns of teaching presence across three categories—Instructional Design and Organization, Facilitating Learning, and Direct Instruction. The findings demonstrated that Direct Instruction was the most prominent category of teaching presence, closely followed by Facilitating Learning and Instructional Design and Organization. In addition, the findings revealed that in a contemporary online course, teaching presence extends beyond asynchronous discussions, manifesting in various elements of the online learning experience. This study underscored the critical role of teaching presence in meeting the needs of learners, particularly nontraditional learners, in an accelerated online course format. This content analysis study highlighted the patterns of teaching presence in course design, development, and delivery, offering valuable insights for both novice and experienced instructors focused on online teaching.